Licensing in the Contemporary Information Economy - Raymond T. Nimmer (Washington University Journal of Law & Policy, 2002)
This Essay examines the role of licensing in our economy and discusses some misconceptions that relate, at least indirectly, to licensing as a means of distributing digital information. There are several basic points. First, discussed in Part II of this Essay is the simple fact that the modern economy, which is characterized by licensing as well as other transfers of informational assets, reflects a vibrant diversity. Demonstrably, there has not been a shrinkage or restriction of availability of information and information-based technology as some allegedly fear, but rather a vibrant expansion and diversification. In a market economy, this diversification and expansion occurs through transactional exchanges. Licensing transactions play an important positive role. Next, Part III examines the definition of a license and the attributes of that type of transaction in contrast to other ways of disseminating information. Part IV turns to the legal foundations for the practice of licensing information, rather than selling copies or giving information away. Finally, in Part V, we discuss the market effect of licensing.
Keywords: Information storage & retrieval systems; Data processing; Licenses; United States; Software license agreements